2010
DOI: 10.1002/adsc.200900618
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Iridium‐Catalyzed Hydrogenation of Trisubstituted Olefins, α,β‐Unsaturated Ketones and Imines with Chiral Benzylic Substituted P,N Ligands

Abstract: The benzylic substituted P,N ligands, diphosphinobenzyloxazolines, showed their high catalytic activity as well as asymmetric induction in the iridium-catalyzed asymmetric hydrogenation of unfunctionalized alkenes, a,b-unsaturated esters, allyl alcohols, a,b-unsaturated ketones, and imines, providing the corresponding chiral products in high ee with high conversion.Keywords: asymmetric hydrogenation; imines; iridium; P,N ligands; unfunctionalized olefins; a,b-unsaturated ketonesThe enantioselective hydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…Contrary to (E)-b,b-disubstituted a,b-unsaturated esters, members of the (Z)-configured cohort have proven very hard to hydrogenate with excellent ee by using N,P-chelated iridium catalysts. [20] We found the hydrogenation of substrate 11 by [(A)*IrA C H T U N G T R E N N U N G (cod)] + A C H T U N G T R E N N U N G [BAr F ] À to be no exception, as an Table 1. Asymmetric hydrogenation of (E)-b,b-disubstituted a,b-unsaturated esters.…”
Section: Resultsmentioning
confidence: 79%
“…Contrary to (E)-b,b-disubstituted a,b-unsaturated esters, members of the (Z)-configured cohort have proven very hard to hydrogenate with excellent ee by using N,P-chelated iridium catalysts. [20] We found the hydrogenation of substrate 11 by [(A)*IrA C H T U N G T R E N N U N G (cod)] + A C H T U N G T R E N N U N G [BAr F ] À to be no exception, as an Table 1. Asymmetric hydrogenation of (E)-b,b-disubstituted a,b-unsaturated esters.…”
Section: Resultsmentioning
confidence: 79%
“…126a Ligand 13a (Figure 4) was used to obtain enantioselectivities over 90% for several β,β-substituted α,β-unsaturated esters. 57 Both the β-methyl (S167) and β-ethyl (S168) derivative could be highly selectively reduced (Table 9, entries 3 and 4), but more significantly, the Z-alkene S169 could be reduced in 92% enantioselectivity (entry 5).…”
Section: αβ-Unsaturated Estersmentioning
confidence: 99%
“…A survey of the literature revealed that asymmetric hydrogenation of these exocyclic imines using iridium catalysts generally afforded low enantioselectivities because the conformational strain, upon coordination to iridium, in the transition state caused by the cyclic structures. [24] An encouraging result of iridium-catalyzed enantioselective hydrogenation of ketimines was reported by Ding and co-workers and up to 98 % ee was achieved with a spirophosphine oxazoline ligand. [25] .…”
Section: Methodsmentioning
confidence: 87%